FORMULASI SEDIAAN SPRAY GEL ANTISEPTIK DARI EKSTRAK ETANOL LIDAH BUAYA (Aloe vera) - Cep Martono; Ine Suharyani (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2018)
Aloe vera potential to developed into antiseptic preparation. One of the preparation is spray gel that easy to use. The aim of this study is to made an antiseptic spray gel containing aloe vera extract. This study devided into 3 part are optimization a gel based, extraction aloe vera and formulation Gel spray containing aloe vera extract. The preparation are evaluated, include organoleptic, homogenity, pH viscosity, spray pattern and hedonic test. The optimization of this preparation showed that the optimization gel base has concentration carbopol 0,25% have viscocity 791,618 cps. Aloe vera exstrack made from maceration with ethano. Spray gel made into 3 formulation are F1, F2, F3 which contains aloe vera extract 8,5%, 10,5%, 12,5%. Viscocity F1 is 28,817 cps, F2 is 19,225, and F3 is 8,058 cps. The result of hedonic test on 53 respondents, based on the order favorite level, F1 is the most preferred preparation with a percentage of 67,54%, then F3 in the 2nd order favored by 64,9% of respondents and the last is F2 with the favorite percentage 64,15%.